Effective Interventions on Improving Elderly's Independence in Activity of Daily Living: A Systematic Review and Logic Model - Motamed-Jahromi, Mohadeseh; Kaveh, Mohammad Hossein (Frontiers in Public Health, 2021)
This systematic review aimed to investigate the types and characteristics of effective interventions when improving the independence of the elderly during activities of daily living. After developing a search strategy, the various databases, including PubMed, Scopus, Cochrane Library, Science Direct, Proquest, and Embase, were searched up to October 16, 2019. The Review Manager 5.1 software was used to determine the risk of bias. The randomized clinical trials were reviewed to find if their interventions' main goal was to improve the elderly's independence in activities of daily living. Data were extracted independently by two authors. Eight randomized controlled trials were included in the final analysis. Three types of interventions were identified and categorized as cognitive training, physical exercises, and multicomponent interventions. All reviewed studies provided evidence of the effectiveness of interventions in improving older people's ability to perform the activities of daily living. However, the lack of uniform measurement indicators to identify and compare the most effective interventions forced us to develop a conceptual framework for designing future interventional research. This conceptual framework included designing tailored interventions, creating an age-friendly environment as well as financial, psychological, and social support. The proposed conceptual framework can also help develop future systematic reviews focusing on a particular intervention type.